PENGARUH KONSERVATISME LABA TERHADAP KOEFISIEN RESPONS LABA - SUARYANA, AGUNG (Jurnal Ilmiah Akuntansi dan Bisnis, 2008)
This research examines earnings response coefficient (ERC) of companies applying conservatism and more optimistic accounting. Conservatism accounting practices are expected to affect companies’ ERC indirectly. Conservative accounting would influence earnings prediction power (Panman and Zhang, 2002). Then, earnings prediction power would influence ERC (Lipe, 1990). The population consists of manufacturing companies listed on the Jakarta Stock Exchange during period of 1999-2005. Sample members of 91 companies are selected using purposive sampling method. Conservative accounting is proxied by earnings/stock return relation measure, earnings/accrual measure, and net asset measures (Watts, 2003). The result shows that companies which apply conservative accounting have weaker earnings prediction power than those which do not. Companies with conservative accounting would have fluctuated earnings and low prediction power of earnings. ERC of companies with conservative accounting are lower than those with more optimistic accounting. Applying conservative accounting would result in fluctuated earnings and lower earnings predictability which is less beneficial in predicting future earnings, thus ERC would be low.
Keywords: conservative accounting, earnings prediction power, earnings response coefficient.